Wounding local hearts? Evidence from an empirical study of UAV attacks by state and non-state actors harming civilian populations. Issue 2 (4th May 2022) - Haugstvedt, Håvard
ABSTRACT: In the "global war on terror, " civilians have been harmed by US and other governments' airstrikes, such as unmanned aerial vehicle (UAV) attacks. This has led to public demand for more transparency into the harm inflicted upon civilian populations. Non-state actors have utilized UAVs for over a decade, and some have armed their UAVs, into kamikaze-style UAVs, or with grenade-dropping capability. This paper compares how UAV attacks by the United States and non-state actors harm civilian populations and how this might influence local or regional support for non-state actors. This study utilized data from 258 UAV attacks by non-state actors. Data on US UAV attacks were obtained from the Bureau of Investigative Journalism. The mean number of casualties and injuries from non-state actors' UAV attacks were 0.17 and 0.43 per attack, respectively, as opposed to 0.42 and 0.14 from US UAV attacks. If non-state actors aim to gain support from local populations, taking their fight to the skies might not be the best strategy. Contrary, civilian harm from non-state actors' attacks might strengthen security forces and create a stronger population-supported counterterrorism effort.